Management of Hand Surgery Services during the Novel Coronavirus Disease 2019 Pandemic - Al-Benna, Sammy (Journal of Hand and Microsurgery, 2020)
Introduction The novel coronavirus disease 2019 (COVID-19) pandemic is an international public health emergency. Health systems must plan for the increasing requirements for critical care during the COVID-19 pandemic. The aim of this article is to offer strategies for hand surgeons to planning and implementing their response during the COVID-19 pandemic and in the subsequent phases to preserve health care system functioning.Materials and Methods Assessment of the principles of management related to COVID-19 management to develop pandemic preparedness and response protocols pertinent to patients, health care workers, and health systems.Results Strategies for the reorganizing hand surgery practice and a set of recommendations that should facilitate the process of rescheduling both out-patient service and surgical activities during the COVID-19 and its subsequent phases are suggested.Conclusion During the COVID-19 pandemic, management of patients requiring specialist care for hand conditions should be adapted to limit the risks associated with the virus without jeopardizing outcomes. These expedient recommendations during extraordinary circumstances are a foundation for further discussion on the topic as the COVID-19 pandemic evolves.
Keywords: practice guideline; health planning guidelines; surgical procedures; hospital outpatient clinics; coronavirus; severe acute respiratory syndrome coronavirus-2; COVID-19; pandemics; hand; hand injuries